2015
DOI: 10.1371/journal.pone.0119030
|View full text |Cite
|
Sign up to set email alerts
|

Double NF1 Inactivation Affects Adrenocortical Function in NF1Prx1 Mice and a Human Patient

Abstract: BackgroundNeurofibromatosis type I (NF1, MIM#162200) is a relatively frequent genetic condition, which predisposes to tumor formation. Apart from tumors, individuals with NF1 often exhibit endocrine abnormalities such as precocious puberty (2,5–5% of NF1 patients) and some cases of hypertension (16% of NF1 patients). Several cases of adrenal cortex adenomas have been described in NF1 individuals supporting the notion that neurofibromin might play a role in adrenal cortex homeostasis. However, no experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It is well known that Nf1 mutations lead to a common autosomal dominant disorder, neurofibromatosis type 1. The neurofibromatosis type 1 patients have an increased incidence of cardiovascular diseases, including obstructive vascular disorders and hypertension [31]. The gamma-aminobutyric acid B-type receptor unit 2 (Gabbr1) expressed in paraventricular nucleus (PVN) is important in controlling sympathetic activity, and its upregulation attenuated sympathoexcitation in chronic heart failure [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Nf1 mutations lead to a common autosomal dominant disorder, neurofibromatosis type 1. The neurofibromatosis type 1 patients have an increased incidence of cardiovascular diseases, including obstructive vascular disorders and hypertension [31]. The gamma-aminobutyric acid B-type receptor unit 2 (Gabbr1) expressed in paraventricular nucleus (PVN) is important in controlling sympathetic activity, and its upregulation attenuated sympathoexcitation in chronic heart failure [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…7 Subclinical brain white matter involvement in CAH is seen as multiple T 2 hyperintense white matter foci, and may be due to hormonal imbalance during brain development or to corticosteroid treatments. 25 Bergamachi et al found a suggestion of association of CAH with demyelinating diseases. 25 Mimics of adrenal cortical hyperplasia Several abnormalities may result in diffuse adrenal enlargement, with apparent maintenance of adreniform shape.…”
Section: Congenital Adrenal Hyperplasia-spectrum Of Imaging Associationsmentioning
confidence: 98%
“…25 Bergamachi et al found a suggestion of association of CAH with demyelinating diseases. 25 Mimics of adrenal cortical hyperplasia Several abnormalities may result in diffuse adrenal enlargement, with apparent maintenance of adreniform shape. These mimics can resemble cortical hyperplasia.…”
Section: Congenital Adrenal Hyperplasia-spectrum Of Imaging Associationsmentioning
confidence: 98%
“…Brain and behavioural phenotypes in NF1 patients may also be influenced by altered levels of circulating glucocorticoids. It has recently been shown that deletion of the NF1 gene in the adrenal cortex increases circulating levels of stress hormones (corticosterone/cortisol) in mouse models and patients [ 92 ]. In individuals with ADHD alone, basal cortisol levels tend to be equivalent to those seen in non-affected individuals [ 93 ] and therefore increased basal stress hormone levels are unlikely to explain the increased propensity to ADHD in NF1.…”
Section: Candidate Cellular Mechanisms Underlying Increased Rates Of mentioning
confidence: 99%